Evaluating mobile apps for sun protection: content analysis and user preferences in a two-part study - Angela M. Rodrigues; Faye L. Doughty; Caroline Charlton; Sarah Woodhouse; Elizabeth Sillence (Health Psychology and Behavioral Medicine)
Background: Sunburn and intermittent sun exposure elevate melanoma skin cancer risk. Sun protection behaviours, including limiting sun exposure, seeking shade, wearing protective gear, and using sunscreen, help mitigate excessive sun exposure. Smartphone apps present a promising platform to enhance these behaviours.Objective: Part 1 aimed to analyse and evaluate the content of mobile apps that encourage sun protection behaviours, focusing on features, and behaviour change techniques (BCTs). Part 2 explored user preferences and usability post-initial use and two weeks later.Results: Part 1 identified 1294 apps; after applying exclusion criteria, 87 apps were downloaded, with 48 included for analysis. The apps presented opportunities for enhancement in their theoretical and evidence basis, and visualisations use (e.g. UV-index). The apps mapped across a total of 12 BCTs (M = 1.71, SD = 1.07; range = 0–5). The most frequently identified BCTs were ‘instruction on how to perform behaviour’ (65%), ‘information about health consequences’ (29%), and ‘prompts/cues’ (27%). In Part 2, participants favoured features supporting knowledge and ease of use. Participants expressed a preference for apps that are free of paid features, advertisements, and external purchases. Tailored advice (e.g. location, skin type) was deemed crucial, particularly for initial exposure. Proactive features integrating behavioural, personal, and contextual information for adaptive and just-in-time sun protection advice were seen as essential for sustaining engagement.Conclusions: Sun protection apps emphasizing knowledge, ease of use, tailored advice, and proactive features are likely to encourage sustained engagement. Suggestions for optimising current and future sun protection apps are provided.